XML-based declarative access control - Steele, R.; Gardner, W.; Dillon, Tharam S.; Erradi, A. (Springer, 2005)
XML, a self-describing and semi-structured data format, is becoming a standard to represent and exchange data between applications across the Web. XML repositories are also starting to be used either to store data or as an interoperability layer for legacy applications and data sources. The widespread use of XML highlights the need for flexible access control models for XML documents to protect sensitive and valuable information from unauthorised access. This paper presents a novel declarative access control model and elaborates how this model allows the expression of access control rules in XML. The paper further introduces the operational semantics of the model by describing the Xplorer engine which supports search-browse-navigate activities on XML repositories. Xplorer takes as inputs XML-based data schema, instance data and access control rules to auto-generate an access control-enabled Web application in accordance with these rules.